Przedsiębiorczość w gospodarce opartej na wiedzy w obszarze metropolitalnym Poznania - Anna Świdurska (Przedsiębiorczość - Edukacja, 2008)
The aim of the paper is to analyse and evaluate the growth of entrepreneurship in the know-ledge-based economy in the Poznań metropolitan area over the recent years (1999-2006) a contribution to the research into the development and transformation of the economy underthe influence of science. The spatial range of the analysis makes it possible to examine therelations under study between the metropolitan core and the surrounding area. For the purposes of the present research, the term entrepreneurship is understood as thetaking of measures intended to create jobs and stimulate economic activity. It is assumed thathigh-tech branches play an important role in job creation. The analysis of the KBE sector embraces high-tech manufacturing sections and the broadercategory of knowledge-intensive services, including high-tech services. The main body of the paper is preceded by interpretations of the essence of a knowledgebased economy, an operational-statistical approach to it, and a general assessment of the deve-lopment of entrepreneurship in the Poznań metropolitan area.